Social media, youths and ethics - Mokhtar, Aida (2017)
Social media for Muslims of OIC countries need to be used ethically. There are several Islamic principles that need to be used as a guide for using social media. Social media has spurred evolutions to take place in Muslim countries notably demonstrated through the Arab Spring. Muslims need to be given the platform of expressing themselves. How this is ideally conducted has to be guided by Islam. Muslims revere Allah SWT and their purpose of life is to worship Him. Hence, in order to gain His blessings, Islamic ethics need to be used for social media.